An Analysis Of Directive Speech Act In The Movie The Legend Of Hercules Manuscript - Kurniadi, Alex, Dra. Malikatul Laila, M. Hum, Dr. Anam Sutopo, M.Hum (2015)
ABSTRACT Alex Kurniadi/A320110102. ANALYSIS OF DIRECTIVE SPEECH ACT IN THE MOVIE THE LEGEND OF HERCULES MANUSCRIPT. Research Paper. English Department. Faculty of Teacher Training and Education. Muhammadiyah University of Surakarta. 2015. This research studies the linguistic forms, types of directive speech act and the intention of directive speech act. The object of this research is the directive speech act in the movie The Legend of Hercules. The type of this research is descriptive qualitative research. The data source of directive speech act in the movie The Legend of Hercules manuscript. In gathering data, the researcher uses observation and documentation methods. To answer the problem statements raise in this research. This researcher implements some theories. To classify the forms, the researcher uses the theory of Frank. To describe the type of the speech act, the researcher uses the theory of Levinson. To describe the intention, the researcher uses the theory of Searle. The result of this study shows that firstly, the most general linguistic form of directive speech act in the movie The Legend of Hercules manuscript is interrogative sentences (16 data or 57,6%), imperative sentences is (10 data or 30,3%), and declarative sentences is (7 data or 21,2%). The intention of directive speech act is commanding (9 data or 27,3%), requesting (19 data or 57,6%), suggesting (3 data or 9,1%) and prohibiting (2 data or 6,1%) Key words: Directive speech, imperative, declarative and interrogative